(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
The educational significance of singing the feeling of homeland in the works of composer Anor Nazarov. Praising patriotism and humanity in songs. Correct understanding of the content of songs, the complex processes of performance and attention to the educational and spiritual content of the works. Deep understanding of the professional content of the song in the art of music, focusing on the poetry and performance skills of the song